Endoscopic red flags for the detection of high-risk serrated polyps: an observational study - Rondagh, E. J. A.; Masclee, A. A. M.; Bouwens, M. W. E.; Winkens, B.; Riedl, R. G.; de Bruïne, A. P.; de Ridder, R.; Kaltenbach, T.; Soetikno, R. M.; Sanduleanu, S. (Endoscopy, 2011)
Background and study aims: In routine practice, colonoscopy may fail to prevent colorectal cancer (CRC), especially in the proximal colon. A better endoscopic recognition of serrated polyps is important, as this pathway may explain some of the post-colonoscopy cancers. In this study, the endoscopic characteristics of serrated polyps were examined. Patient and methods: This was a cross-sectional, single-center study of all consecutive patients referred for elective colonoscopy during 1 year. The endoscopists were familiarized with the detection and treatment of nonpolypoid colorectal lesions. Serrated polyps were classified into high risk serrated polyps, defined as dysplastic or large ( ≥ 6 mm) proximal nondysplastic serrated polyps, and low risk serrated polyps including the remaining nondysplastic serrated polyps. Advanced colorectal neoplasms were defined as multiple (at least three), ≥ 10 mm in size, high grade dysplastic adenomas or CRC. Results: A total of 2309 patients were included (46.1 % men, mean age 58.4 years), of whom 2.5 % (57) had at least one high risk serrated polyp and 13.9 % (322) had at least one advanced neoplasm. Overall, serrated polyps were more often nonpolypoid than adenomas (16.2 % vs. 11.1 %; P = 0.002). In total, 65 high risk serrated polyps were found, of which 43.1 % (28) displayed a nonpolypoid endoscopic appearance. Patients with advanced neoplasms were more likely to have synchronous high risk serrated polyps than patients without advanced neoplasms: OR 3.66 (95 % CI 2.03 – 6.61, P < 0.001). Conclusions: High risk serrated polyps are frequently nonpolypoid and are associated with synchronous advanced colorectal neoplasms. Advanced colorectal neoplasms may therefore be considered red flags for the presence of high risk serrated polyps. Detection, diagnosis, and treatment of high risk serrated lesions may be important targets to improve the quality of colonoscopic cancer prevention.